Mediate Work Ability And Burnout Personal Resources, Job Resources And Job Demands On Work Engagement - Yanita Hendarti; Hwihanus Hwihanus (Cita konsultindo, 2023)
Human Resources (HR) in the current era of modernization are required to be able to adapt to world developments, adaptations are made so that companies can compete globally. Human resources are considered as a very valuable organizational asset, human resources can be continuously developed to achieve sustainable success for every organization. personal resources, job resources and job demands are matters related to HR, HR is the center of attention and support for the organization in order to survive because HR plays a major role in every activity and activity of the organization in order to achieve organizational goals. What is the relationship and influence of personal resources, job resources and job demands with burnout and work ability as mediation on work engagement becomes a problem that must be revealed, this is the aim of this research. The method of writing this research is by using qualitative methods and literature studies or library research. Reviewing theories and reviewing literature books that are in accordance with the theories discussed, especially the scope of human resource management (HRM). Besides that, it also analyzes reputable and non-reputable scientific articles and journals. All scientific articles are sourced from Google Scholar. Based on the discussion, the researcher found several findings related to the relationship and influence of personal resources, job resources and job demands with burnout and work ability as mediators on work engagement.